2021
DOI: 10.3390/ijms22063259
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function of Ion Channels Regulating Sperm Motility—An Overview

Abstract: Sperm motility is linked to the activation of signaling pathways that trigger movement. These pathways are mainly dependent on Ca2+, which acts as a secondary messenger. The maintenance of adequate Ca2+ concentrations is possible thanks to proper concentrations of other ions, such as K+ and Na+, among others, that modulate plasma membrane potential and the intracellular pH. Like in every cell, ion homeostasis in spermatozoa is ensured by a vast spectrum of ion channels supported by the work of ion pumps and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(70 citation statements)
references
References 186 publications
(339 reference statements)
1
60
0
Order By: Relevance
“…Sperm cells under different pH dilutions have differences in motor activity, DNA damage degree, and expression of apoptotic protein (You et al, 2017), including membrane surface ion channel (Ca 2+ , k + , Na + , etc.) activity (Miller et al, 2015;Nowicka-Bauer and Szymczak-Cendlak, 2021) and sperm tail VSP protein. The level of phosphorylation varies (Zhelay et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Sperm cells under different pH dilutions have differences in motor activity, DNA damage degree, and expression of apoptotic protein (You et al, 2017), including membrane surface ion channel (Ca 2+ , k + , Na + , etc.) activity (Miller et al, 2015;Nowicka-Bauer and Szymczak-Cendlak, 2021) and sperm tail VSP protein. The level of phosphorylation varies (Zhelay et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Calogero et al [57] similarly reported that progesterone increased BCF and VCL, but decreased LIN and STR of motile spermatozoa. Furthermore, the observed improvements in the LM subpopulations' motility parameters may be a result of either intracellular pH or proper balancing of intracellular ions, and not necessarily activation of progesterone CatSper Ca 2+ influx [58].…”
Section: Progesteronementioning
confidence: 97%
“…The seemingly inability of progesterone to rapidly induce higher hyperactivation and AR percentages in the LM subpopulations could be related to slowness or deficiency in the formation of Ca 2+ signaling domains. To successfully achieve capacitation by CatSper, a quadrilateral arrangement of four pore-forming α-subunits needs to develop, which structurally organizes unique Ca 2+ signaling domains along the flagellum [58,64]. The absence or alteration of genes that prevent the formation of this heterotetrametric CatSper complex will thereby prevent capacitation [58,64].…”
Section: Progesteronementioning
confidence: 99%
“…Progesterone activates the capacitation process; however, it has been noted that PRG-induced acrosome reaction also can happen [11]. Progesterone-induced changes are mediated by intracellular mechanisms associated with protein kinase C and voltage-gated Ca 2+ channels [12]. By stimulating or inhibiting protein kinases A, C, G and tyrosine kinase, it has been shown that progesterone induces the acrosome reaction via tyrosine kinase and protein kinase C, but in horse sperm cells this process does not depend on protein kinases A, C and bicarbonate [13].…”
Section: Introductionmentioning
confidence: 99%